Floral Metabolism of Sugars and Amino Acids: Implications for Pollinators' Preferences and Seed and Fruit Set. Issue 4 (6th October 2017) - Borghi, Monica; Fernie, Alisdair R.
Abstract : New discoveries open up future directions in the study of the primary metabolism of flowers.